Quadruple Photoresponsive Functionality in a Crystalline Hybrid Material: Photochromism, Photomodulated Fluorescence, Magnetism and Nonlinear Optical Properties - Han, Song‐De; Liu, Ai‐u; Wei, Qi; Hu, Ji‐Xiang; Pan, Jie; Wang, Guo‐Ming (Chemistry : a European journal, 2021)
As promising photoresponsive materials and potential smart materials, hybrid photochromic materials (HPMs), especially for crystalline HPMs (CHPMs), have been broadly explored for their potential in inheriting the merits of each constituents, and intriguing photomodulated functionality. Hitherto, the photoresponsive functionality in explored CHPMs mainly concentrate on dyad combination. By contrast, triple or quadruple photoresponsive properties are very rare because of the limited compatibility of multiple photoresponsive functionality in a single system. In this work, the electron‐transfer (ET) and crystal engineering strategies were utilized to predesign CHPMs with multiple photoresponsive properties via the collaboration of paramagnetic metal ion (Dy3+), electron‐donor (ED) ligand (benzene‐1,2,3‐tricarboxylic acid, H3BTA) and electron‐acceptor (EA) ligand (1,10‐phenanthroline, phen). The resulting complex [Dy(BTA)(phen)2]⋅2H2O (1) shows hybrid chain with the intrachain Dy3+ ions bridged and chelated by tricarboxylate and phen ligands, respectively. After photostimuli, the ET between tricarboxylate and phen results in photogenerated radicals and the resultant quadruple photoresponsive properties. Considering the abundant resources of paramagnetic metal ions, ED‐ and EA‐ligands, this work provides a general method to construct CHPMs with multiple photoresponsive performances via the collaboration of each unit under the guidance of ET and crystal engineering strategies. A crystalline hybrid material is reported with quadruple photoresponsive functionality, which shows photochromism, photomodulated fluorescence, magnetism, and second‐order nonlinear optical properties. This work provides a general method to construct hybrid photochromic materials with multiple photoresponsive performances.